Жанр психологического романа в украинской и английской литературе первой половины XIX века (Е. Гребинка, Т. де Квинси) - Chyk, Denys; Kucher, Vasyl (Slavia Centralis, 2020)
In the article, E. Grebinka’s novel The Doctor is analysed in comparison with the novel by Thomas de Quincey Confessions of an English Opium-Eater. The authors prove that the novel by E. Grebinka is the first psychological novel in Ukrainian literature. It is noted that among the specific and typologically common features of the analysed texts are as follows: the authors’ attention to the formation of the adult character; a conflict between society and the sentimental introvert personality type; the depiction of the irrational manifestation of the protagonists’ unconscious sphere through the anima projection; psychological changes in the personality structure due to alcohol or drug consumption.